The relationship between asymmetry changes in the slope frequency of bioelectrical activity of the gluteus maximus muscles and experience in short track speed skating athletics - Konieczny, M.; Pakosz, P.; Domaszewski, P.; Skorupska, E. (Isokinetics and Exercise Science, 2025)
BACKGROUND: In short track speed skating, there is asymmetric fatigue of the gluteus maximus (GM) muscle resulting from the technique of skating. Scientific reports confirm the relationship between muscle fatigue and its change in the slope frequency of bioelectrical activity.